Answer:
D = -4/7 = - 0.57
C = 17/7 = 2.43
Step-by-step explanation:
We have the following two equations:
![3C + 4D = 5\ --------------- eqn (1)\\2C + 5D = 2\ --------------- eqn (2)](https://img.qammunity.org/2022/formulas/physics/college/85t75t8eaf02erxlgw4mitd8tuvztnqhs3.png)
First, we isolate C from equation (2):
![2C + 5D = 2\\2C = 2 - 5D\\C = (2 - 5D)/(2)\ -------------- eqn(3)](https://img.qammunity.org/2022/formulas/physics/college/8bodycaqs20zvgpfdk6gp2w7ajv028jsbs.png)
using this value of C from equation (3) in equation (1):
![3((2-5D)/(2)) + 4D = 5\\\\(6-15D)/(2) + 4D = 5\\\\(6-15D+8D)/(2) = 5\\\\6-7D = (5)(2)\\7D = 6-10\\\\D = -(4)/(7)](https://img.qammunity.org/2022/formulas/physics/college/6rytuumm3pi1l48zvqh3euost6n8ea68le.png)
D = - 0.57
Put this value in equation (3), we get:
![C = (2-(5)((-4)/(7) ))/(2)\\\\C = ((14+20)/(7))/(2)\\\\C = (34)/((7)(2))\\\\C = (17)/(7)\\](https://img.qammunity.org/2022/formulas/physics/college/1g6wq9rztmw8zyw08b533ci7xyjlvlwew4.png)
C = 2.43